Differences in presentation, diagnosis and management of heart failure in women. A scientific statement of the Heart Failure Association of the ESC - Rosano, Giuseppe M C; Stolfo, Davide; Anderson, Lisa; Abdelhamid, Magdy; Adamo, Marianna; Bauersachs, Johann; Bayes-Genis, Antoni; Böhm, Michael; Chioncel, Ovidiu; Filippatos, Gerasimos; Hill, Loreena Michelle; Lainscak, Mitja; et al. (My University, 2024)
Despite the progress in the care of individuals with heart failure (HF), important sex disparities in knowledge and management remain, covering all the aspects of the syndrome, from aetiology and pathophysiology to treatment. Important distinctions in phenotypic presentation are widely known, but the mechanisms behind these differences are only partially defined. The impact of sex-specific conditions in the predisposition to HF has gained progressive interest in the HF community. Under-recruitment of women in large randomized clinical trials has continued in the more recent studies despite epidemiological data no longer reporting any substantial difference in the lifetime risk and prognosis between sexes. Target dose of medications and criteria for device eligibility are derived from studies with a large predominance of men, whereas specific information in women is lacking. The present scientific statement encompasses the whole scenario of available evidence on sex-disparities in HF and aims to define the most challenging and urgent residual gaps in the evidence for the scientific and clinical HF communities.
Keywords: Women; Device; Heart failure; Medical therapy; Risk factor